2021
DOI: 10.2217/fon-2021-0469
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of anticholinergic burden in older patients with and without cancer

Abstract: Aim: To compare anticholinergic burden (ACB) in older patients with and without cancer and evaluate the effects of ACB on geriatric syndromes. Methods: A total of 291 patients from the geriatric clinic and 301 patients from the oncology clinic were evaluated. ACB <2 was categorized as low ACB and ACB ≥2 was categorized as high ACB. A comprehensive geriatric assessment was performed on patients from the geriatric clinic. Results: ACB scores were significantly higher in patients without cancer compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…For example, malnutrition may be common in older cancer patients because of nausea and vomiting that may develop due to chemotherapy ( 10 ). In addition, drugs that can be used to control symptoms and side effects such as nausea, fatigue, and pain may increase the frequency of polypharmacy ( 11 ). While geriatric syndromes are multifactorial, the presence of cancer also contributes to the development of these syndromes ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, malnutrition may be common in older cancer patients because of nausea and vomiting that may develop due to chemotherapy ( 10 ). In addition, drugs that can be used to control symptoms and side effects such as nausea, fatigue, and pain may increase the frequency of polypharmacy ( 11 ). While geriatric syndromes are multifactorial, the presence of cancer also contributes to the development of these syndromes ( 2 , 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Anticholinergic drug load is the cumulative effect of drugs that can produce anticholinergic side effects. 7 The complications such as falls, delirium, and frequent hospitalization may often be seen due to the effect of anticholinergic drugs used. 7 In a few studies, it has been reported that exposure to anticholinergic drugs may also cause sleep disorders, which may increase side effects.…”
mentioning
confidence: 99%
“…7 The complications such as falls, delirium, and frequent hospitalization may often be seen due to the effect of anticholinergic drugs used. 7 In a few studies, it has been reported that exposure to anticholinergic drugs may also cause sleep disorders, which may increase side effects. 8 However, to date, there is no study to investigate the relationship between anticholinergic drugs and EDS.…”
mentioning
confidence: 99%
See 2 more Smart Citations